Assessing the Social Implications of Remittances in Nepal - Ghimire, Dipesh Kumar (KMC Research Journal, 2024)
Remittances, constituting monetary and non-monetary transfers from migrants to their home countries, have emerged as a crucial driver of economic growth in developing nations. Nepal, witnessing a surge in remittance inflows since the 1980s amidst global economic liberalization, is a pertinent case study. This paper delves into the ramifications of remittance-induced consumption on Nepal's economic landscape, traversing historical trajectories and contemporary realities. Despite the substantial influx of remittances, a significant portion is funneled into everyday consumption, constraining its potential for catalyzing productive investment. Through a meticulous examination of diverse data sources and prior research, this study underscores the imperative for efficacious policies aimed at redirecting remittances towards sectors conducive to fostering sustainable economic development. While existing literature predominantly scrutinizes remittances through an economic lens, this research endeavors to illuminate the understudied social implications, particularly pertaining to consumption patterns. By comprehensively analyzing the impacts of consumption-based remittances on household dynamics, community structures, and cultural practices, this article seeks to contribute to a nuanced understanding of Nepal's socio-economic fabric.